Increasing power coefficient of small wind turbine over a wide tip speed range by determining proper design tip speed ratio and number of blades - Yilmaz, Oktay (SAGE PUBLICATIONS LTD, 2022)
This paper proposes a design strategy based on an understanding of basic rotor aerodynamics principles to achieve aerodynamically efficient small wind turbine rotor by determining proper design tip speed ratio (TSR) and number of blades. In the design and performance analyses of rotors, the blade element momentum (BEM) method was employed in conjunction with the Viterna-Corrigan post-stall model and Buhl's wake state model. BEM simulations use the Re number dependent airfoil aerodynamic coefficients derived through Xfoil panel code. Reduced design tip speed ratio increased rotor solidity and hence blade Reynolds number. The width of the optimum TSR range, on the other hand, was found to decrease when the design TSR was less than a certain threshold. At high tip speeds, rotors with optimum design TSR were able to maintain an almost constant and near-ideal axial induction factor, resulting widest optimum TSR range for high aerodynamic efficiency. Increasing number of blades (B) increased C-P,C-max, but further increase in B lowered rotor efficiency due to reduced blade Re number. Based on CFD results, 5-blade SD7032 rotor with a design TSR of 4 achieved 12.3% higher C-P,C-max compared to 0.9 m diameter 3-blade experimental reference rotor. Maximum achievable power coefficient of infinitely many-bladed ideal rotor with design TSR of 4 is 0.559, while C-P,C-max of 5-blade SD7032 rotor is 0.492.
Keywords: Small wind turbine; aerodynamic efficiency; design tip speed ratio; number of blades; blade element momentum; axial induction factor; ideal rotor; Xfoil; computational fluid dynamics; SHAPE OPTIMIZATION; PERFORMANCE; MODEL; AIRFOIL; CURVE; ROTOR; HAWT; Engineering